Pengalaman Komunikasi Interpersonal Cosplayer: (Studi Fenomenologi atas Komunitas CCW di DKI Jakarta) - Chairunisa, Audina; Azwar, Azwar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The cosplay trend has quickly developed into a subculture in Indonesia, especially among teenagers. This research aims to see how the cosplay phenomenon influences the development of interpersonal communication. This research uses a qualitative method with a phenomenological approach to achieve this goal. This approach was adopted to understand cosplayers' experiences and interpersonal communication perspectives thoroughly. Data was collected using several stages, including in-depth interviews with cosplayers, direct observation of their interactions in various cosplay scenarios, and joint documentation with them after the interview process was completed. Data processing and analysis are linked to interpersonal communication theory according to Joseph A. Devito to achieve effective interpersonal communication with the main characteristics, namely openness, empathy, supportive attitude, positive attitude, and equality. The results of this research show that there are differences in interpersonal communication between cosplayers when wearing costumes and when they are not. In addition, this research found that cosplay activities help cosplayers' self-development, especially in terms of communication skills.